2010
DOI: 10.4028/www.scientific.net/msf.638-642.3418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strain Path on Microstructure Evolution of Low Carbon Steels

Abstract: Changes in strain path represent one of the most important processing parameters that characterise hot metal forming processes. In the present study, the effect of strain path change on dynamic recrystallisation, strain-induced precipitation processes and phase transformation behaviour in plain carbon and Nb-microalloyed steels was investigated. To assess the effect of strain-path change, forward/forward and forward/reverse torsion tests were conducted. It has been shown that the strain reversal delays the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…For microalloyed steels, it has been reported the strain reversal retards the recrystallisation and Nb(C,N) precipitation kinetics [4]. However, early research by authors found that the strain path change has very mild effect on the microstructure evolution through phase transformation [5]. In this work, the focus will be placed on the direct strain path effect during deformation below the austenite recrystallisation-stop temperature in terms of its influence on the phase transformation behaviour.…”
Section: Introductionmentioning
confidence: 98%
“…For microalloyed steels, it has been reported the strain reversal retards the recrystallisation and Nb(C,N) precipitation kinetics [4]. However, early research by authors found that the strain path change has very mild effect on the microstructure evolution through phase transformation [5]. In this work, the focus will be placed on the direct strain path effect during deformation below the austenite recrystallisation-stop temperature in terms of its influence on the phase transformation behaviour.…”
Section: Introductionmentioning
confidence: 98%